Stanje zagotavljanja digitalnih zbirk v slovenskih organizacijah s področja kulturne dediščine - Lesjak, Blaž (Knjižnica, 2016)
Purpose: The digitisation of cultural heritage and provision of digital collections are gaining importance in the missions of memory institutions. The ENUMERATE Core Survey 3 tried to establishing the status and progress on digitisation of cultural heritage across Europe. The article presents the survey methodology and results thus comparing the achievements of Slovenian and European participating institutions. The assessment of current status is made on the basis of findings and a possible explanation is sought. Methodology/Approach: The research methodology was established as a result of the ENUMERATE project. It includes a set of statistical indicators. Data were collected in the ENUMERATE Core Survey 3 using a web questionnaire. The survey took place in the year 2015. There were 1.030 sample institutions from 32 countries, 54 participating institutions were from Slovenia. Data are presented and analysed using descriptive statistical methods. Results: Statistical indicators for Slovenian institutions and comparison to other Europe%s cultural heritage institutions are presented. The indicators analysed are addressing the digitisation activity, size of collections, object types, digitisation progress, strategic approach, availability of metadata and objects, collecting born digital heritage, measuring use of digital collections, reasons for providing digital access, channels of provision to digital collections, digital preservation, budgets, costs, staff and funding. In general, the results indicate that participating Slovenian institutions are lagging behind the participating European countries. Research limitation: Findings have a limited validity due to non-representativeness of the sample. Originality/Practical implications: Findings can be used for the assessment of current status and devising actions and strategies, however the research limitation has to be considered.
Keywords: cultural heritage; digitalizacija; digitization; evaluation; kulturna dediščina; project ENUMERATE; vrednotenje; methodology; metodologija; projekt ENUMERATE; statistical data; statistični podatki; Slovenia; Slovenija